Pressing Issues of Unlawful Application of Artificial Intelligence - Yuryevna Bokovnya, Alexandra; Rustamovich Begishev, Ildar; Ilduzovna Khisamova, Zarina; Izmailovich Bikeev, Igor; Leonidovna Sidorenko, Elina; Davletovna Bersei, Diana (International Journal of Criminology and Sociology, 2022)
The article discusses the problematic aspects of the implementation and application of artificial intelligence technology at the present stage of its development. The authors provide definitions of this technology, with its essential properties revealed based on their analysis. Criminological forecasting helps identify groups of crimes most likely to be committed through the use of artificial intelligence. The authors believe that at present there are not sufficient grounds for distancing ourselves from the issue of the subject of criminal liability in case of damage to public relations directly by the AI, but there are no circumstances due to which its resolution would not be delayed. The system of criminal law relations must be built based on scientifically developed provisions. The problems of criminal legal regulation, in terms of the impossibility of criminalizing and penalizing socially dangerous acts committed by artificial intelligence, are revealed. The legislator is asked to develop and adopt legal acts regulating the creation, operation, and use of artificial intelligence.